Guel Music and Dance as Agents of Social Change: Strengthening Social Cohesion and Cultural Sustainability in Central Aceh - Herdiati, Dian; Nurlaili, Nurlaili; Musnaini , Sabariah (Universitas Negeri Semarang, 2025)
This research aims to explore and analyse the role of Gayo music and dance performances as agents of social change in strengthening social cohesion and cultural sustainability within the Gayo community in Central Aceh. The research is motivated by the importance of the performing arts as a medium for preserving cultural identity and uniting communities, particularly in the face of the challenges posed by globalization, which threatens the sustainability of local traditions. The urgency of the research lies in the need to understand concrete strategies for utilizing traditional arts for social purposes, as well as to fill the gap in the literature regarding the unique elements of Guel music and dance in the context of social change. The research method employed was a mixed-methods approach with a sequential explanatory design, combining a quantitative survey of 176 participants with a qualitative phenomenological study of 25 participants. The study’s results showed that participation in Guel performances, particularly through the “Saturday Arts” and “Annual Festival” programs, significantly increased the community’s sense of belonging, cultural pride, and social involvement. Quantitative data analysis showed an increase in governance and conservation indicators by 13.6% and 23.6%, respectively, while qualitative data revealed Guel’s role in value education, gender inclusivity, and intercultural dialogue. The discussion relates this finding to Bourdieu’s theory of social capital, confirming that Guel functions as a social glue (bonding capital), a bridge between groups (bridging capital), and a transformer of cultural capital into social capital. This research recommends the development of inclusive cultural policies, the integration of traditional arts into the educational curriculum, and a community-based governance approach to ensure the sustainability of Guel music and dance as an intangible cultural heritage and a unifying force for society.